Hassan Hanafiâ€™s Response to Western Hegemony in Muqaddimah FÄ« â€˜Ilmi al-IstighrÄb Through Hegemony Theory of Gramsci - Feriyadi Feriyadi; Syamsul Hadi (Universitas Ahmad Dahlan, 2018)
This is a literature study on Hassan Hanafi's response to the hegemony of Western civilization by using hegemony theory of Gramsci. One of the responses discussed in this research is the discussion of Occidentalism. Hanafi introduced the notion of Occidentalism as a study of the West from the eyes of the East. He acknowledges that the West is a major entrant and also a source of scientific knowledge in our consciousness. Therefore, the West occupies a very important position. Such an important position according to Hanafi received less serious response by Muslim intellectuals. Hanafi's Occidentalism was intended to confront Western civilization's hegemony of the East consciousness. With Occidentalism it is expected that the Eastern position which has been used as the object of the study may change, that is to be an observer or researcher. In addition, Hanafiâ€™s Occidentalism wants to end the Western myth as a representation and the holder of world civilization supremacy. Western studies of the East have so far led to a stereotype that the rise and fall of a civilization can be measured by the benchmarks of Western civilization. Such an attitude, eventually foster inferiority to other civilizations. The main source of this study is Hanafiâ€™s book entiteled Muqaddimah fÄ« â€˜Ilmi al-IstighrÄb. The paper found that Hanafiâ€™s Occidentalism is not as a counterpart of Orientalism, not as a tool in fighting against Western civilization, nor as anti-Western, but the Occidentalism used as a means to position the West as one of civilizations without narrow fanaticism, without blind thought, while enhancing local wisdom and Eastern tradition amid advances in technology and science.